Experimental investigations on the implosion characteristics of thin cylindrical aluminium-alloy tubes. (September 2020) - Muttaqie, Teguh; Hyun Park, Sang; Min Sohn, Jung; Cho, Sang-Rai; Sik Nho, In; Han, Soonhung; Lee, Phill-Seung; Sik Cho, Yoon
Highlights: Implosion tests are conducted using water only and the combination of water and nitrogen gas. The ovality and thickness unevenness of the test models are measured. The effects of pressurising rates on the ultimate strength of the test models are investigated. Dynamic pressures in terms of short duration pulses are also monitored during the collapse event. The effect of geometric parameters on the ultimate strengths are numerically conducted. Abstract: Experimental studies are conducted to investigate the implosion characteristics of thin cylindrical aluminium-alloy tubes. The effects of various parameters that generate different responses on the implosion behaviours are investigated. Aluminium-alloy tubes are fabricated from a 6061-T6 material and designed in the range of 2.5–6.7 length-to-diameter ratios; wall thickness-to-diameter ratios are varied from 55 to 69. The geometric imperfection parameters, defined as the initial ovality and thickness unevenness, are considered. Two different pressurising media, i.e., water only and the combination of water and nitrogen gas are employed. In addition small- and medium-sized of pressure chamber are utilised to clarify the pressure drop after the ultimate strength reached. Furthermore, non-linear finite element analyses, benchmarked for quantitative validation and comparison of the imploded tubes, are conducted. The numerical benchmark quantities are initial ovality, thickness unevenness, and air-backed fluid cavity parameters. The results of these experiments indicated that the effects of combined water and nitrogen can reproduce a constant pressure environment similar as actual undersea conditions, but the combined pressuring media can reduce the pressuring rate.